Pengaruh Elektronik Word of Mouth terhadap Minat Beli Skincare dan Kosmetik Lokal secara Online melalui Kepercayaan - Uyun, Nadia Azkal; Sutiono, Heru Tri; Sugandini, Dyah (CV. Strata Persada Academia, 2023)
This research seeks to observe and test consumers' online purchasing interests based on the role of trust and Electronic Word of Mouth (E-WOM). This research uses PLS (Partial Least Square) based on SEM (Structural Equation Modeling). The sample in this research was 188 consumers from 5 regions in the Special Region of Yogyakarta. This research uses a purposive sampling technique in data collection. The criteria for respondents are women aged 20-30 years. The results of this research found that there is a positive and significant direct influence of both E-WOM and trust on online buying interest in local skincare and cosmetics in Indonesia, especially in Yogyakarta. So, it can be said that interest or intention to buy online depends on both E-WOM and trust. However, the mediating role of trust was also tested in this study, and the results were positive and significant. So, it can be said that online purchasing intentions, apart from being directly dependent on E-WOM, can also be mediated by trust.